A deficiency or developmental defect in paneth cells may contribute to the pathogenesis of appendicitis in children (Annals of Medical Research, 2023)
Aim: The aim of this study was to investigate whether there were differences in the Paneth cells between children with acute appendicitis (AA) and those with normal appendix (NA), and to reveal the distribution and morphological changes in Paneth cells in appendix inflammation.Materials and Methods: The data of 63 patients who underwent appendectomy diagnosed with acute appendicitis between January 2021 and December 2022, including age, gender, operative diagnosis, and postoperative histopathological examination results, were analyzed retrospectively. To evaluate the distribution and changes of Paneth cells throughout AA and NA groups, samples with hematoxylin and eosin (H&E)-stained sections were obtained from the Department of Histopathology's archives. Selected blocks were stained with Masson-Trichrome. The number of Paneth cells and the degree of granular density in the appendicitis tissues were statistically evaluated and compared with the results of the control group.Results: A total of 63 appendectomies were performed, including 31 incidental appendectomies and 32 performed for acute appendicitis. There were no statistically significant differences between the groups that underwent surgery for AA and the NA in terms of gender and age (p>0.05). It was observed that the number of Paneth cells and granule density decreased significantly in acute appendicitis (AA) group (p
Keywords: Appendicitis; Children; Paneth cell